Are ecosystem service bundles useful for mountainous landscape function zoning and management? A case study of Bailongjiang watershed in western China. (January 2022) - Gong, Jie; Jin, Tiantian; Liu, Dongqing; Zhu, Yuehua; Yan, Lingling
Graphical abstract: Highlights: Clear spatial changes in ecosystem services (ESs) and their relationships were found. Apparent differences of dynamic correlation between ESs pairs were revealed. Land-use, agriculture and husbandry are critical for mountainous ESs. An integrated landscape functional zoning method was developed based on ES bundles. Abstract: Managing ecosystem service (ES) bundles to synergize their benefits is a crucial but challenging task for landscape planning and sustainable development. However, few studies have focused on ES bundles for landscape management in complex mountainous social–ecological systems. In this study, we quantified four ESs, food supply, soil conservation, water conservation, and habitat quality, in the Bailongjiang watershed (BLJW) in western China by using multi-source geospatial data and related ecological and societal information from 1990 to 2016. We found significant spatial and temporal changes in ES patterns and their relationships measured in 1990, 2002, 2010, and 2016. We found both strong positive and negative relationships ( P < 0.01) among ESs in the four time-intervals. The BLJW was divided into five landscape functional zones by the newly integrated method to link ES bundles and social–ecological indicators for landscape management. Land use, population density, agriculture, and animal husbandry were found to have greatly affected the ES pattern and the comprehensive ecosystem service benefit of the BLJW. We suggest governing the mountainous social–ecological system with the goal of building a watershed community of common destiny with a shared future for ESs and for integrated landscape management.